OTA study on Indian health care : hearing before the Subcommittee on Health and the Environment of the Committee on Energy and Commerce, House of Representatives, Ninety-ninth Congress, second session, February 20, 1986. - United States. Congress. House. Committee on Energy and Commerce. Subcommittee on Health and the Environment. (Washington : U.S. G.P.O. : For sale by the Supt. of Docs., Congressional Sales Office, U.S. G.P.O., 1986)
"Serial no. 99-97." Mode of access: Internet.